Liver Transplantation for Hepatic Epithelioid Hemangioendothelioma: The Canadian Multicentre Experience - Carmine G Nudo; Eric M Yoshida; Vincent G Bain; Denis Marleau; Phil Wong; Paul J Marotta; Eberhard Renner; Kymberly D Watt; Marc Deschênes (Canadian Journal of Gastroenterology)
INTRODUCTION: Hepatic epithelioid hemangioendothelioma (HEHE) is a rare entity. At the present time, there is no standardized effective therapy. Liver transplantation (LT) has emerged as a treatment for this rare tumour.